Pemanfaatan Data Pengaduan SP4N LAPOR Dalam Perumusan Kebijakan Publik Di Pemerintah Kabupaten Madiun - Tony Hartono; Slamet Muchsin; Afifuddin Afifuddin (Jayapangus Press, 2026)
The effective utilisation of citizen generated complaint data as a strategic input for evidence informed public policy continues to present challenges for local government institutions. This study investigates the utilisation of SP4N LAPOR complaint data in the public policy making processes of the Madiun Regency Government. SP4N LAPOR is Indonesia’s national public service complaint management system designed to enable citizens to submit feedback, grievances, and recommendations directly to relevant government agencies. Employing a descriptive qualitative research design, the study draws on data collected through in-depth interviews, non-participant observation, and document analysis of relevant institutional materials. The findings indicate that, despite a marked increase in SP4N LAPOR complaint submissions from 2020 to 2024, the integration of this data into formal public policy formulation remains limited. Complaint data are predominantly used for administrative reporting and performance monitoring rather than as analytical evidence to inform policy decisions. Key constraints include institutional fragmentation, limitations in technical system interoperability, and inadequate analytical capacity within human resources. These factors collectively diminish the potential of complaint data to support evidence-based governance. Consequently, this study recommends strengthening analytical competencies among public officials, institutionalising a dedicated complaint data analysis unit, and integrating SP4N LAPOR with planning and budgeting platforms to enhance the utilisation of citizen feedback for responsive and data driven public policy making. Unlike previous research that used SP4N LAPOR as an instrument for the effectiveness of complaint services, this study places complaint data as the analytical foundation for evidence informed public policy at the local government level.